KUALITAS PELAYANAN PENDIDIKAN DALAM MENGANALISIS KEPUASAN MAHASISWA PADA PROGRAM STUDI PENDIDIKAN MATEMATIKA - Atica Puspitaningtyas; Rubhan Masykur; Siska Andriani (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
Service quality is an evaluation of the results of the process of comparing the services that consumers have received with the service they expect. Based on the results of observations that have been made found several student complaints about poor service quality, including in the form of facilities or infrastructure. The purpose of this study was to determine the level of student satisfaction with the quality of education services with the servqual method. This research is a descriptive qualitative study. The data analysis technique uses the servqual method and the importance performance analysis (IPA) method. The results in this study show that students are not satisfied with the educational services provided by the mathematics education department, whereas in the science analysis there are several service items which are included in the top priority namely timely attendance, security, friendliness, structuring the lecture room, AC facilities, LCD facilities and worship facilities.